Karakteristik siswa generasi z dan kebutuhan akan pengembangan bidang bimbingan dan konseling - Ali Mansur; Ridwan Ridwan (Universitas Hamzanwadi, 2022)
Generation Z is a generation that, since childhood, has been familiar with technology. In reality, many millennial children are now found drifting in the vortex of social media, where they experience phubbing, an addiction to smartphones where they are willing to hurt their friends around them, which is a challenge for the world of education. Educational institutions need to be ready to carry out their duties to build a character who is faithful and pious, good character, knowledgeable, healthy, and so on. Guidance and Counseling teachers (counselors) need to realize that solving individual problems is complicated because each violation will harden the heart. Hence, this study aims to map the characteristics of generation Z students with their needs for guidance and counseling. The characteristics of Generation Z are a continuation of the millennial generation, where they are already small familiar with digital media. They need to undergo education and guidance appropriate to their time. Can the characteristics of Generation Z be served and their needs met with services in guidance and counseling? This question was answered by conducting qualitative research in a document study, and data analysis was carried out using Recouer's interpretation technique. The analysis results show that Generation Z's characteristics are relevant to services in the fields of Guidance and Counseling. It is just that the four areas that have been implemented so far, namely the personal, social, study, and career fields, need to be added by prioritizing the spiritual field and the field of family guidance